The disappearance of communal culture and the forced assimilation of urban values. Analysis of its representation in the narratives of rurality in Spain (Anclajes, 2026)
Resumen: The communal peasant cultures have been erased in the course of a silent ethnocide that has lasted for centuries and whose ultimate consequences we are experiencing in the present. The story of these forgotten people has been traced on the margins of the great written accounts and has had to be traced in their margins, that is, in what others have said about them. The current literatures of rurality in Spain have had to consider this contradiction and have returned, on more than a few occasions, to the traumatic event of exodus: to the fracture of the code. After laying the theoretical foundations of this process, we will analyse its materialisation in the work of Cristina Sánchez-Andrade.
Keywords: Literatures of the Rurality; Peasant; Collectivism; Agriculture Land; Cristina Sánchez - Andrade